Nutraceutical Potential of Tinctures from Fruits, Green Husks, and Leaves of Juglans regia L. - Urszula Gawlik-Dziki; Agata Durak; Łukasz Pecio; Iwona Kowalska (The Scientific World Journal)
The aim of this study was to assess the phenolic composition and nutraceutical potential of tinctures from fruits in two stages of maturity (F3, younger; F25, older), green husks (GH), and leaves (L) of Juglans regia L. In all extracts gallic, protocatechuic, 3-caffeoylquinic, 3-ρ-coumaroylquinic, 4-caffeoylquinic, 4-ρ-coumaroylquinic, and ρ-coumaric acids and quercetin-3-O-deoxyhexoside were detected using UPLC-MS technique. Caffeic acid hexoside I and quercetin-3-O-deoxyhexoside I have been identified in GH tincture. The highest ability to chelate Fe2+ was observed for GH tincture (EC50 = 71.01±3.55 mg FM/mL), whereas the lowest was observed (EC50 = 131.06±6.55 mg FM/mL) for F3 tincture. The highest reducing power was found for F3 and F25 (EC50 = 32.47±1.53 and 36.07±1.72 mg FM/mL, resp.). Ability of tinctures to prevent lipids against oxidation was relatively low. The highest activity (EC50 = 126.49±6.32 mg FM/mL) was determined for F25. Tested tinctures showed relatively high antiradical activity—EC50 values ranged from 100.56±5.03 to 129.04±6.45 mg FM/mL for L and F25, respectively. The results obtained suggest that J. regia can be a source of bioactive compounds with antioxidant properties.